The last frontier : imagining other worlds, from the copernican revolution to modern science fiction, Karl S. Guthke, Cornell University Press, Ithaca y Londres, 1992, 402 páginas - Lemarchand, Guillermo A. (1994)
Fil: Lemarchand, Guillermo A. Universidad de Buenos Aires. Centro de Estudios Avanzados; Argentina.